The “Scale A” factor and the growth of colombian economy - Zarur Ramos, Alberto Luis (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2012)
The purpose of this article is to prove that, in Colombia, economic growth has not been enough neither to improve incomeper capita, nor has it been constant, mainly due to the fact that it has been highly supported by the growth of labor and capital, while the contribution of factor productivity has been negative. In order to achieve this purpose, the document is structured in two parts. First of all, a theoretical reflection is carried out around Cobb-Douglas’s function of production, to show the existence of a residue beyond the growth of employment rate and capital, and also to highlight the fact that the existence of that residue, the so-called A Factor, is the key for the sustainable growth in the classically and recently developed countries, particularly Asian countries. Secondly, the useless role that factorial productivity hasplayed in Colombian growth for the past thirty years is evidenced, as well as the conclusions resulting from this situation.